2008
DOI: 10.4161/cbt.7.10.6538
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and testing of bevacizumab radioimmunoconjugates with Bismuth-213 and Bismuth-205 / Bismuth-206

Abstract: Bevacizumab, a humanized anti-VEGF monoclonal antibody has shown promise in various clinical trials. We report the development and testing of Bi-213 (an a-emitting radionuclide) labeled bevacizumab for in vitro and in vivo studies using two different chelators viz cDTPA and CHX-A″.The developed labeling method showed high labeling yields of 93.6% and 89.7% for cDTPA and CHX-A″ respectively and the results were reproducible. The in vitro and in vivo stability tests were carried out using Bi-213 and long half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The high stability is essential since free 111 In can be transchelated to transferrin, decreasing tumor-to-blood ratio and, consequently, contrast of imaging of VEGF in tumors. This is in agreement with data by Rizvi et al, who showed that the CHX-A"-DTPA conjugate was far more stable than cDTPA conjugate as a as its retention and kinetics in blood is concerned [15].…”
Section: Resultssupporting
confidence: 93%
“…The high stability is essential since free 111 In can be transchelated to transferrin, decreasing tumor-to-blood ratio and, consequently, contrast of imaging of VEGF in tumors. This is in agreement with data by Rizvi et al, who showed that the CHX-A"-DTPA conjugate was far more stable than cDTPA conjugate as a as its retention and kinetics in blood is concerned [15].…”
Section: Resultssupporting
confidence: 93%
“…23 The uptake data for 166 Ho-DOTA-bevacizumab is comparable with 89 Zr-bevacizumab. 9 Both show medium uptake for liver and lower amounts in the intestine. However, the bone uptake difference is the result of Zr free cation affinity due to metabolization of the complex.…”
Section: Ho-dota-bevacizumab Biodistribution In Rat Tissuesmentioning
confidence: 99%
“…The Allen group in Australia has actively studied the efficacy of 213 Bi-labeled mAb as TAT agents [77][78][79][80][81]. The mAb 9.2.27 has a high specificity for human melanoma cell surfaces.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%